Synthetic fertilization reduction with compost and irrigation optimization on maize stem rot (Fusarium spp) - López Valenzuela, Blanca E. (2014)
Maize is the most important grain crop in Mexico due to the largest area grown and as the main source of feeding nationwide; being Sinaloa de major producer. The same crop over repeated seasons has favored disease proliferation of stem and ear rot mainly attributed to Fusarium spp which represents a risk potential so that growers are warned top pay close attention to crop management. With the purpose of evaluating the effect of synthetic fertilization with compost and irrigation on maize stem and ear rot at Valle del Fuerte. Field experiments were conducted in the growing season of 2009 at INIFAP. The experiments were arranged under a split plot in randomized complete block design with three replicates. At the end of the season, it was found that fertilization or irrigation by themselves did not have any significant effect in yield and phenology variables evaluated. However, incidence on stem rot which was evaluated at 53 days after planting was that of 100%. Moreover, there were significant differences regarding severity of rotten ears when less irrigation was applied. Finally, morphological study showed that the main agent associated in maize stem rot was Fusarium verticilliodes. In contrast to that of ear rot that the main agents involved were Apergillus spp, Penicillum pinophilum, and with a higher incidence was Fusarium verticilliodes.